1990
DOI: 10.1038/sc.1990.9
|View full text |Cite
|
Sign up to set email alerts
|

Early intermittent self-catheterisation after spinal cord injury

Abstract: SummaryAn evaluation has been made of intermittent self-catheterisation (lSC) carried out by 25 paraplegic patients early after injury. The results were compared with those of intermittent catheterisation (IC) done in another 48 paraplegic patients by a catheter team. No significant difference was found regarding the rate of urinary infection or the incidence of urethral trauma. The final outcome of bladder training did not differ significantly between the two groups. Patients on self-catheterisation went home… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
5

Year Published

1992
1992
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 8 publications
0
13
0
5
Order By: Relevance
“…22,39 Cross infection is less if IC during hospitalization is done by a catheter team 40 or by the patients themselves. 41 As residual urine plays a role in infection, attention must be made to empty the bladder completely. 22 Treatment of UTI is necessary if the infection is symptomatic.…”
Section: Resultsmentioning
confidence: 99%
“…22,39 Cross infection is less if IC during hospitalization is done by a catheter team 40 or by the patients themselves. 41 As residual urine plays a role in infection, attention must be made to empty the bladder completely. 22 Treatment of UTI is necessary if the infection is symptomatic.…”
Section: Resultsmentioning
confidence: 99%
“…Each of these has its own hazards; but clean self intermittent catheterisation has emerged as the method of choice in recent years. [7][8][9] The commonest reservation against CIC ex pressed by many patients and unfortunately also by some physicians concerns the poss ible risk of introducing infection. In our study, we found that positive urine cultures patients that antibacterial prophylaxis signi ficantly reduced the probability of "laborat ory', but not of 'clinical' infection.…”
Section: Discussionmentioning
confidence: 99%
“…An early start of self–catheterization, if feasible, allows more freedom and independence of the disabled patient [8]. The main aim of bladder rehabilitation for many SCI patients is not necessarily to be ‘catheter free’, which was popularized in the 1960s and 1970s [9, 10], but to preserve renal function by low pressure storage and being dry and continent if possible.…”
Section: Discussionmentioning
confidence: 99%